Special issue introduction: historical and cultural perspectives of food on the fairgrounds. (15th March 2021) - Miller, Bonnie M.
ABSTRACT: This special issue of Food, Culture & Society examines how fairs and expositions–at local, regional, national, and international levels–have reflected and shaped perceptions of food production, marketing, and consumption for mass audiences. It will consider the perspectives of fair organizers, publicists, exhibitors, concessionaires, restaurateurs, and participants in constructing and experiencing the diversity of food cultures on the fairgrounds and the social situations fairs and expositions can foster. These essays will examine food on the fairgrounds from a multi-sensory perspective, thinking about food not only as something ingested, but also engaged through display, art, and performance. This special issue seeks to place in conversation the scholarship on fairs/expositions with the history of food cultures around the world, the dynamics of its exhibition and display, and its promotion of community cohesion and culinary consciousness in order to demonstrate the importance of these mass cultural events as sites where local, regional, national, and corporate culinary identities are simultaneously made and unmade.